2018
DOI: 10.1029/2018je005556
|View full text |Cite
|
Sign up to set email alerts
|

UV Dayglow Variability on Mars: Simulation With a Global Climate Model and Comparison With SPICAM/MEx Data

Abstract: A model able to simulate the CO Cameron bands and the CO 2+ UV doublet, two of the most prominent UV emissions in the Martian dayside, has been incorporated into a Mars global climate model. The model self‐consistently quantifies the effects of atmospheric variability on the simulated dayglow for the first time. Comparison of the modeled peak intensities with Mars Express (MEx) SPICAM (Spectroscopy for Investigation of Characteristics of the Atmosphere of Mars) observations confirms previous suggestions that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…During dust storm periods, the altitude of the peak dayglow emissions moves up with larger amplitude than predicted by the MCD. The peak altitude of the two emissions was also modeled as a function of the solar longitude by González‐Galindo et al () for different Martian years than analyzed in this work. González‐Galindo et al () found that the upward displacement of the altitude of the airglow layers predicted by the MCD during dust seasons was less than the SPICAM observations by as much as 16 km.…”
Section: Discussionmentioning
confidence: 99%
“…During dust storm periods, the altitude of the peak dayglow emissions moves up with larger amplitude than predicted by the MCD. The peak altitude of the two emissions was also modeled as a function of the solar longitude by González‐Galindo et al () for different Martian years than analyzed in this work. González‐Galindo et al () found that the upward displacement of the altitude of the airglow layers predicted by the MCD during dust seasons was less than the SPICAM observations by as much as 16 km.…”
Section: Discussionmentioning
confidence: 99%
“…The IUVS NO density retrieval relies heavily on the removal of the bright, blended features that have obscured its detectability in the MUV until now. The spectral analysis would benefit from high‐resolution laboratory measurements of the Cameron bands from all sources of excitation ( e.g ., Fox & Dalgarno, ; González‐Galindo et al, ) to better assess the quality of our two‐temperature fit. Despite this approximation in the band model, Figures d and d indicate that the weak NO γ band dayglow features can be retrieved if we limit our analysis to the narrow spectral region where the γ bands most efficiently fluoresce.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the source of NO on Mars and Earth is molecular nitrogen (N 2 ), but on Mars, the N 2 mixing ratio at the surface is only 3% (Franz et al, ) which reduces its upper atmospheric abundance compared to Earth. Furthermore, the middle ultraviolet dayglow in the upper atmosphere of Mars is dominated by the bright and spectrally complex carbon monoxide (CO) Cameron bands (a 3 Π ➔ X 1 Σ + ), which are excited primarily from photodissociation and electron impact dissociative excitation of carbon dioxide (CO 2 ; González‐Galindo et al, ). These two obstacles have combined to obscure the detection of NO dayglow on Mars heretofore (Barth et al, ).…”
Section: Motivationmentioning
confidence: 99%
“…Models indicate that a major source of excitation of the CO (a 3 Π) state near the peak in the dayglow and aurora is electron impact on CO 2 (Bhardwaj & Jain, 2013; Gérard et al., 2019; Leblanc et al., 2006). However, there has been recent evidence that electron impact on CO may also play an important role on Mars in the production of the CB above the emission peak (González‐Galindo et al., 2018, 2019). A consequence is that the Cameron emission scale height may be significantly larger than the CO 2 scale height and that the use of the topside scale height of CB limb profile to determine the temperature is not straightforward.…”
Section: Discussionmentioning
confidence: 99%